Misdiagnosis of Behçet's disease presented with intracardiac mass as inflammatory myofibroblastic tumor - Hale Ünal Aksu; Pınar Yazıcı; Kürşat Öz; Nevzat Uslu; Ersin Erek (KARE Publishing, 2014)
Behçet's disease is a chronic multisystem inflammatory disorder. There are limited data about cardiac involvement, but it is seen rarely. Herein, we present a 33-year-old male patient with heart failure secondary to a right ventricular mass. It was first diagnosed as inflammatory myofibroblastic tumor (IMT) histopathologically. During the postoperative follow-up, a thrombus was detected at the interatrial septum, and the patient was reevaluated. The diagnosis was possible Behçet's disease, and the mass, previously reported as IMT, was determined to be an organizing thrombus with a mixture of granulation tissue and thrombotic material.